PENGARUH PENGGUNAAN MEDIA REALIA TERHADAP KEMAMPUAN MENGENAL MAKANAN SEHAT PADA ANAK - Dea Imelda Siregar; Dior Manta Tambunan (Universitas Murni Teguh, 2026)
Many children still have limited ability to recognize and distinguish between healthy and unhealthy foods. This condition may be influenced by learning methods that are less concrete and less engaging for young children. The use of realia media as a learning method is considered effective because it involves real objects that can be directly seen and touched, making it easier for children to understand the concept of healthy food. The objective of this study is to determine the effect of using realia media on the ability to recognize healthy food among children at TK Tunas Harapan Mandiri Medan. This study employed a quantitative approach with a pre-experimental one group pretest–posttest design. The sampling technique used was purposive sampling, involving 52 children aged 5–6 years. Data were collected using a questionnaire measuring children’s ability to recognize healthy food before and after the implementation of learning activities using realia media. Bivariate Data analysis was conducted by Wilcoxon Test. The results showed an improvement in children’s ability to recognize healthy food after the implementation of learning using realia media. Statistically, the use of realia media had a significant effect on children’s ability to recognize healthy food, with a p-value < 0.05. There is a significant effect of using realia media on the ability to recognize healthy food among children. Realia media can be used as an effective alternative learning method for nutrition education in early childhood. It is recommended for future researchers to add variables such as the role of parents and children's attitudes towards healthy food to enrich the research results. Abstrak Masih banyak anak yang belum mampu mengenali dan membedakan makanan sehat dan tidak sehat dengan baik. Kurangnya pemahaman ini dapat dipengaruhi oleh metode pembelajaran yang kurang konkret dan kurang menarik bagi anak. Penggunaan media realia sebagai media pembelajaran dinilai efektif karena menggunakan benda nyata yang dapat dilihat dan disentuh secara langsung, sehingga memudahkan anak dalam memahami konsep makanan sehat. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan media realia terhadap kemampuan mengenal makanan sehat pada anak TK Tunas Harapan Mandiri Medan. Penelitian ini merupakan penelitian kuantitatif dengan desain pre-eksperimental one group pretest–posttest. Teknik pengambilan sampel menggunakan purposive sampling dengan jumlah responden sebanyak 52 anak usia 5–6 tahun. Pengumpulan data menggunakan kuesioner kemampuan mengenal makanan sehat pre-post intervensi pembelajaran menggunakan media realia. Analisis data bivariat menggunakan Uji Wlcoxon. Hasil penelitian menunjukkan adanya peningkatan kemampuan mengenal makanan sehat pada anak setelah diberikan pembelajaran menggunakan media realia. Secara statistik, penggunaan media realia menunjukkan pengaruh yang signifikan terhadap kemampuan mengenal makanan sehat dengan p-value < 0,05. Terdapat pengaruh yang signifikan antara penggunaan media realia terhadap kemampuan mengenal makanan sehat pada anak. Media realia dapat digunakan sebagai alternatif media pembelajaran yang efektif dalam edukasi gizi anak usia dini. Disarankan pada peneliti selanjutnya untuk menambahkan variabel peran orang tua dan sikap anak terhadap makanan sehat untuk memperkaya hasil penelitian.